Perovskite SrLaFeO4 / FOOH heterojunction electrochemical catalyst as well as preparation method and application thereof
By growing FeOOH film on the surface of perovskite SrLaFeO4, the heterojunction structure of SrLaFeO4/FeOOH was constructed, and the problem of insufficient activity and stability of perovskite oxide catalysts in water decomposition was solved, and efficient and stable anode oxygen evolution reaction performance was achieved. .
Patent Information
- Application Number
- CN202411564424.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-07
AI Technical Summary
The existing perovskite oxide catalysts have low inherent conductivity and catalytic activity in water decomposition, which limits their application in overall water decomposition, especially in anode oxygen evolution reaction (OER) with slow reaction kinetics and low activity. .
By growing FeOOH films on the surface of perovskite SrLaFeO4, a heterojunction structure of SrLaFeO4/FeOOH was constructed, and a catalyst was prepared by sol-gel method and water bath heating strategy, which promoted the perovskite lattice to participate in the oxygen process and hydroxyl adsorption.
The OER activity and stability of perovskite catalysts are improved, which is manifested as a low overpotential and a small Tafel slope, which significantly improves the energy conversion efficiency.
Smart Images

Figure CN119392298A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical catalysis, and in particular, relates to a perovskite SrLaFeO4 / FOOH heterojunction electrochemical catalyst and a preparation method and application thereof. Background Art
[0002] Hydrogen is a green and clean energy carrier because of its high gravimetric energy density and zero carbon content. The main source of hydrogen production is industrial steam reforming of natural gas and water into carbon dioxide and hydrogen, but the low energy efficiency of the conversion process and the presence of carbon-containing residues result in high cost and poor purity of hydrogen products. To address this problem, electrochemical water splitting is becoming an encouraging approach to produce hydrogen. Electrolytic water splitting involves two important half reactions, namely the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER). Compared with the cathode hydrogen evolution reaction (HER), the anode oxygen evolution reaction (OER) reaction has a more complex reaction pathway and much slower reaction kinetics. Therefore, the development of efficient and stable OER electrocatalysts and greatly improved OER activity and stability will greatly improve the energy conversion efficiency. Ir-based and Ru-based materials are the best electrocatalysts in OER. However, the high cost and scarcity of these materials limit their feasibility for commercial applications.
[0003] Among many candidate catalysts, perovskite oxides have been widely studied, and many perovskite electrocatalysts for HER and OER have been developed. However, the low intrinsic conductivity and catalytic activity of most perovskite oxides have hindered the practical application of perovskite oxides in overall water splitting. Therefore, the activity and stability of perovskite oxides still need to be improved to effectively utilize renewable and clean energy. As an environmentally friendly material with abundant earth resources, iron-based compounds, especially FeOOH, have great prospects in the electrocatalytic oxidation of water due to their strong adsorption of hydroxyl groups and H2O.
[0004] Some studies have shown that hydroxyl groups have thermodynamic advantages in certain perovskites. However, OH filling is much slower than lattice oxygen leaching, which limits the performance of OER and even causes drastic surface structural changes. Therefore, accelerating the participation of perovskite lattices in oxygen processes and promoting hydroxyl adsorption will be a direct and effective way to improve the catalytic performance of perovskites. However, the existing technology has not yet touched on this topic. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a perovskite SrLaFeO4 / FOOH heterojunction electrochemical catalyst and a preparation method and application thereof, wherein lanthanum nitrate, cobalt nitrate and strontium nitrate are used as lanthanum source, cobalt source and strontium source respectively, and a sol-gel method and a water bath heating strategy are adopted to prepare the perovskite SrLaFeO4 / FOOH heterojunction electrochemical catalyst.
[0006] The present invention improves the OER activity of the SrLaCoO4 perovskite catalyst by growing a FeOOH film on the perovskite surface, and the optimized SrLaCoO4 / FeOOH catalyst has a lower overpotential and a smaller Tafel slope. XPS and electrochemical impedance spectroscopy analysis show that the excellent OER catalytic performance of SrLaCoO4 / FeOOH can be attributed to the synergistic effect of SrLaCoO4 and FeOOH, which promotes strong electronic interactions, promotes charge transfer, and improves active sites.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] The preparation method of the perovskite SrLaFeO4 / FOOH heterojunction electrochemical catalyst comprises the following steps:
[0009] (1) Precursor preparation
[0010] La(NO3)3·6H2O, Co(NO3)2·6H2O, Sr(NO3)2, citric acid and ethylene glycol were added to deionized water and ultrasonically treated for 30 minutes to obtain a uniform nitrate mixed solution. Subsequently, the mixed solution was heated until a brown sol was formed. The brown solid obtained by drying the brown sol in an oven is the prepared SrLaFeO4 precursor.
[0011] (2) Primary pyrolysis
[0012] The precursor obtained in step (1) is placed in a muffle furnace, heated to 500°C in air at a certain heating rate and maintained for 24 hours, then taken out and ground, and then heated to 900°C for a second time and maintained for several hours. After cooling to room temperature, the product (SrLaFeO4) is collected.
[0013] (3) Construction of heterojunction
[0014] Weigh a certain amount of K2FeO4 and dissolve it in NaOH solution. Stir for 10 minutes to obtain K2FeO4 solution. Add NaOH to adjust the hydrolysis rate of K2FeO4. Continue to weigh SrLaFeO4 and add it to the K2FeO4 solution and ultrasonicate for 10 minutes to obtain a uniform solution. Heat the obtained solution in a water bath and stir for 24 hours. Wash the obtained sample with deionized water and ethanol to obtain the final product.
[0015] Furthermore, the ratio of the amount of La(NO3)3·6H2O, Co(NO3)2·6H2O, Sr(NO3)2, citric acid, ethylene glycol and deionized water is 1mmol:1mmol:1mmol:6mmol:3mL:100mL.
[0016] Furthermore, the oven drying parameters in step (1) are: drying in an oven at 100° C. for 2 hours.
[0017] Furthermore, in step (2), the heating rate is 2°C / min; and the holding time at 900°C is 12h.
[0018] Furthermore, the concentration of the NaOH solution in step (3) is 3 mol / L.
[0019] Furthermore, in step (3), the molar ratio of K2FeO4 to SrLaFeO4 is 1:1.
[0020] Another object of the present invention is to provide a perovskite SrLaFeO4 / FOOH heterojunction electrochemical catalyst prepared by the above preparation method, and the application of the catalyst in anode oxygen evolution reaction (OER).
[0021] Beneficial effects of the present invention:
[0022] The present invention provides a method for preparing a perovskite SrLaFeO4 and FeOOH heterojunction electrochemical catalyst, and applies the method to an OER catalyst under alkaline conditions. Compared with the prior art, the method combines the crystalline SrLaFeO4 with the amorphous FeOOH to obtain a heterostructure, so that the active area of the prepared catalyst is increased. The SrLaFeO4 / FeOOH heterojunction electrochemical catalyst was prepared by water bath heating. Due to the synergistic effect between SrLaFeO4 and FeOOH, the catalyst exhibits excellent and stable OER catalytic performance under alkaline conditions. At 10 mA cm -2 At a current density of 1.38 Å, only 354 mV overpotential is required, and the Tafel slope is small (61.06 mV·dec -1 ). The present invention not only provides a simple and feasible preparation strategy for regulating perovskite-type catalytic materials, but can also be used as a reference for further designing and constructing other high-efficiency catalytic materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The present invention will be further described below in conjunction with the accompanying drawings.
[0024] Figure 1 is a flow chart of the preparation method of the present invention;
[0025] Figure 2 The X-ray diffraction (XRD) comparison diagrams of the products obtained in Example 1, Comparative Examples 1-2 and the standard card;
[0026] Figure 3(a) Raman spectra of SrLaCoO4, FeOOH and the product obtained in Example 1; (b) Infrared spectra of SrLaCoO4, FeOOH and the product obtained in Example 1; (c) N2 adsorption curves of SrLaCoO4 and the product obtained in Example 1;
[0027] Figure 4 It is the XPS spectrum of SrLaCoO4 and the product obtained in Example 1;
[0028] Figure 5 Energy dispersive X-ray surface distribution (EDS-mapping) diagram of different elements of the product obtained in Example 1;
[0029] Figure 6 The OER performance test data of five catalysts, namely, the products obtained in Example 1, Comparative Examples 1-2, SrLaFeO4 and FeOOH, are as follows: (a) LSV curve, (b) mass activity ratio at 1.65 V, (c) Tafel slope graph, (d) double layer capacitance, (e) EIS graph, and (f) stability curve determined by chronopotentiometry. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The preparation method flow chart of the present invention is as follows Figure 1 shown.
[0032] Example 1
[0033] 1mmol (433.4634mg) La(NO3)3·6H2O, 1mmol (291.0591mg) Co(NO3)2·6H2O, 1mmol (212.6934mg) Sr(NO3)2, 6mmol (1.1585mg) citric acid and 3ml ethylene glycol were added to 100mL deionized water and ultrasonically treated for 30min to obtain a uniform nitrate mixed solution. Subsequently, the mixed solution was heated until a brown sol was formed. The brown sol was dried in an oven at 100℃ for 2 hours to obtain a brown solid, which was the prepared SrLaFeO4 precursor.
[0034] The obtained SrLaFeO4 precursor was placed in a muffle furnace, heated to 500°C at a heating rate of 2°C / min in air and maintained for 24 hours, then taken out and ground, and then heated to 900°C for a second time and maintained for 12 hours. After cooling to room temperature, the product was collected.
[0035] Weigh 1 mmol of K2FeO4 and dissolve it in 50 mL of 3M NaOH solution, stir for 10 min to obtain a K2FeO4 solution, and add NaOH to regulate the hydrolysis rate of K2FeO4. Continue to weigh 1 mmol of SrLaFeO4 and add it to the K2FeO4 solution and ultrasonicate for 10 min to obtain a uniform solution. Then heat the obtained solution in a water bath and stir for 24 hours. Wash the obtained sample with deionized water and ethanol to obtain the final product, which is calculated as SrLaCoO4 / FeOOH-1:1.
[0036] Comparative Example 1
[0037] 1mmol (433.4634mg) La(NO3)3·6H2O, 1mmol (291.0591mg) Co(NO3)2·6H2O, 1mmol (212.6934mg) Sr(NO3)2, 6mmol (1.1585mg) citric acid and 3ml ethylene glycol were added to 100mL deionized water and ultrasonically treated for 30min to obtain a uniform nitrate mixed solution. Subsequently, the mixed solution was heated until a brown sol was formed. The brown sol was dried in an oven at 100℃ for 2 hours to obtain a brown solid, which was the prepared SrLaFeO4 precursor.
[0038] The obtained SrLaFeO4 precursor was placed in a muffle furnace, heated to 500°C at a heating rate of 2°C / min in air and maintained for 24 hours, then taken out and ground, and then heated to 900°C for a second time and maintained for 12 hours. After cooling to room temperature, the product was collected.
[0039] Weigh 2mmol of K2FeO4 and dissolve it in 50mL of 3M NaOH solution. Stir for 10min to obtain K2FeO4 solution. Add NaOH to regulate the hydrolysis rate of K2FeO4. Continue to weigh 1mmol of SrLaFeO4 and add it to the K2FeO4 solution and ultrasonicate for 10min to obtain a uniform solution. Then heat the obtained solution in a water bath and stir for 24h. Wash the obtained sample with deionized water and ethanol to obtain the final product, which is recorded as SrLaCoO4 / FeOOH-1:2.
[0040] Comparative Example 2
[0041] 1mmol (433.4634mg) La (NO3) 3·6H2O, 1mmol (291.0591mg) Co (NO3) 2·6H2O, 1mmol (212.6934mg) Sr (NO3) 2, 6mmol (1.1585mg) citric acid and 3ml ethylene glycol were added to 100mL deionized water and ultrasonically treated for 30min to obtain a uniform nitrate mixed solution. Subsequently, the mixed solution was heated until a brown sol was formed. The brown sol was dried in an oven at 100°C for 2 hours to obtain a brown solid, which was the prepared SrLaFeO4 precursor.
[0042] The obtained SrLaFeO4 precursor was placed in a muffle furnace, heated to 500°C at a heating rate of 2°C / min in air and maintained for 24 hours, then taken out and ground, and then heated to 900°C for a second time and maintained for 12 hours. After cooling to room temperature, the product was collected.
[0043] Weigh 0.5mmol of K2FeO4 and dissolve it in 50mL of 3M NaOH solution, stir for 10min to obtain K2FeO4 solution, and add NaOH to regulate the hydrolysis rate of K2FeO4. Continue to weigh 1mmol of SrLaFeO4 and add it to the K2FeO4 solution and ultrasonicate for 10min to obtain a uniform solution. Then heat the obtained solution in a water bath and stir for 24h. Wash the obtained sample with deionized water and ethanol to obtain the final product, which is recorded as SrLaCoO4 / FeOOH-2:1.
[0044] The performance tests were carried out on the products obtained in Example 1, Comparative Examples 1-2, SrLaFeO4 and FeOOH: Figure 2 The X-ray diffraction (XRD) comparison diagram of the products obtained in Example 1 and Comparative Examples 1-2 and the standard card; Figure 3 The Raman spectra, infrared spectra and N2 adsorption curves of the product obtained in Example 1 and SrLaCoO4 and FeOOH are shown; Figure 4 Shown is the XPS spectrum of the product obtained in Example 1 and SrLaCoO4; Figure 5 This is the energy dispersive X-ray surface distribution (EDS-mapping) diagram of different elements of the product obtained in Example 1.
[0045] The products obtained in Example 1 and Comparative Examples 1-2, SrLaFeO4 and FeOOH were applied to OER catalytic water electrolysis to produce hydrogen, as follows:
[0046] (1) Pretreatment of working electrode
[0047] The working electrode used was a straight glassy carbon electrode (GCE, 3 mm in diameter), which was carefully polished on the suede surface with micron-grade Al2O3 powder. Each polishing time was 5 min. The polished glassy carbon electrode was rinsed clean of the polishing powder on the surface with deionized water, then cleaned with ethanol, and finally dried under a dust-free infrared lamp.
[0048] (2) Modified glassy carbon electrode
[0049] 10 mg of each of the five catalysts prepared in Example 1, Comparative Example 1, and Comparative Example 2, SrLaCoO4 / FeOOH-1:1, SrLaCoO4 / FeOOH-1:2, SrLaCoO4 / FeOOH-2:1, SrLaFeO4, and FeOOH, were weighed and dispersed in 70 μL of a mixed solution of Nafion (5 wt%) and 1 mL of anhydrous ethanol, and then dispersed evenly by ultrasonic dispersion to obtain dispersants of five different catalysts. 3 μL of the catalyst dispersion was dripped onto a polished glassy carbon electrode three times, and dried under an infrared lamp to obtain a catalyst-modified electrode.
[0050] (3) Electrochemical test
[0051] Electrochemical tests were performed on the electrodes modified with five catalysts to compare their OER catalytic performance and analyze the effect of different FeOOH contents on the OER catalytic performance of the catalysts. The electrochemical test used a classic three-electrode system, in which the catalyst-modified straight glassy carbon electrode was the working electrode, the carbon rod was the counter electrode, and the Hg / HgO electrode was the reference electrode. 1.0 mol L -1 KOH was used as the electrolyte to carry out OER performance tests under alkaline conditions, including linear sweep voltammetry (LSV), Tafel slope, cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and stability tests.
[0052] The OER performance test results of different catalysts in this application example are as follows: Figure 6 shown. Figure 6 a is the LSV test curve of catalysts such as SrLaCoO4 / FeOOH-1:2, SrLaCoO4 / FeOOH-1:1, SrLaCoO4 / FeOOH-2:1, SrLaFeO4 and FeOOH, from which the overpotential, mass activity and Tafel slope are calculated. Figure 6 b Comparison of the mass activities of the prepared SrLaCoO4 / FeOOH-1:2, SrLaCoO4 / FeOOH-1:1, SrLaCoO4 / FeOOH-2:1, SrLaFeO4 and FeOOH catalysts. Figure 6c Comparison of the Tafel slopes of the prepared SrLaCoO4 / FeOOH-1:2, SrLaCoO4 / FeOOH-1:1, SrLaCoO4 / FeOOH-2:1, SrLaFeO4 and FeOOH catalysts. -2 At a current density of 1.3 Å, the overpotential of SrLaCoO4 / FeOOH-1:1 is 354 mV, which is much lower than that of SrLaCoO4 / FeOOH-1:2, SrLaCoO4 / FeOOH-2:1, SrLaFeO4 and FeOOH. The Tafel slope of SrLaCoO4 / FeOOH-1:1 is 61.06 mV·dec -1 , lower than SrLaCoO4 / FeOOH-1:2, SrLaCoO4 / FeOOH-2:1, SrLaFeO4 and FeOOH. Figure 6 d. The double-layer capacitance is calculated by CV test data. By comparison, it can be seen that the double-layer capacitance of SrLaCoO4 / FeOOH-1:1 is the highest. Figure 6 From the EIS spectrum of e, it can be seen that SrLaCoO4 / FeOOH-1:1 has the smallest charge transfer resistance. The catalyst was tested for stability for 120 hours, and the curve is as follows Figure 6 f, indicating that it has good stability.
[0053] The above specific implementation method part specifically introduces the analytical method involved in the present invention. It should be noted that the above introduction is only to help those skilled in the art better understand the method and ideas of the present invention, rather than limiting the relevant content. Without departing from the principle of the present invention, those skilled in the art may also make appropriate adjustments or modifications to the present invention, and the above adjustments and modifications shall also fall within the scope of protection of the present invention.
Claims
1. A method for preparing a perovskite SrLaFeO4 / FOOH heterojunction electrochemical catalyst, characterized in that: The following steps are involved: (1) Precursor preparation La(NO3)3·6H2O, Co(NO3)2·6H2O, Sr(NO3)2, citric acid and ethylene glycol were added to deionized water and subjected to ultrasonic treatment for 30 minutes to obtain a uniform nitrate mixed solution; then, the mixed solution was heated until a brown sol was formed, and the brown sol was dried in an oven to obtain a brown solid, which was the prepared SrLaFeO4 precursor; (2) Primary pyrolysis The precursor obtained in step (1) is placed in a muffle furnace, heated to 500°C in air at a certain heating rate and maintained for 24 hours, then taken out and ground, and then heated to 900°C for a second time and maintained for several hours, and after cooling to room temperature, the product (SrLaFeO4) is collected; (3) Construction of heterojunction A certain amount of K2FeO4 was weighed and dissolved in NaOH solution, and stirred for 10 minutes to obtain a K2FeO4 solution. NaOH was added to adjust the hydrolysis rate of K2FeO4. SrLaFeO4 was further weighed and added to the K2FeO4 solution, and ultrasonicated for 10 minutes to obtain a uniform solution. The obtained solution was heated in a water bath and stirred for 24 hours. The obtained sample was washed with deionized water and ethanol to obtain the final product.
2. The method for preparing the perovskite SrLaFeO4 / FOOH heterojunction electrochemical catalyst according to claim 1, characterized in that: The usage ratio of La(NO3)3·6H2O, Co(NO3)2·6H2O, Sr(NO3)2, citric acid, ethylene glycol and deionized water is 1mmol:1mmol:1mmol:6mmol:3mL:100mL.
3. The method for preparing the perovskite SrLaFeO4 / FOOH heterojunction electrochemical catalyst according to claim 1, characterized in that: Oven drying parameters in step (1): drying in an oven at 100° C. for 2 hours.
4. The method for preparing the perovskite SrLaFeO4 / FOOH heterojunction electrochemical catalyst according to claim 1, characterized in that: In step (2), the heating rate is 2°C / min; the holding time at 900°C is 12h.
5. The method for preparing the perovskite SrLaFeO4 / FOOH heterojunction electrochemical catalyst according to claim 1, characterized in that: The concentration of the NaOH solution in step (3) is 3 mol / L.
6. The method for preparing the perovskite SrLaFeO4 / FOOH heterojunction electrochemical catalyst according to claim 1, characterized in that: The molar ratio of K2FeO4 to SrLaFeO4 in step (3) is 1:
1.
7. Perovskite SrLaFeO4 / FOOH heterojunction electrochemical catalyst, characterized in that it is prepared according to the preparation method according to any one of claims 1-6.
8. Use of the perovskite SrLaFeO4 / FOOH heterojunction electrochemical catalyst according to claim 7 in an anode oxygen evolution reaction.
Citation Information
Patent Citations
Universal method for effectively improving catalytic performance of perovskite catalysts
CN109351357A
Oxygen evolution catalyst, preparation method thereof and electrolysis device
CN116334675A
Alkaline seawater electrolysis catalyst and preparation method thereof
CN118756190A